2020
DOI: 10.33899/ijvs.2019.125653.1123
|View full text |Cite
|
Sign up to set email alerts
|

The inhibitory role of effective microorganisms on the growth of pathogenic bacteria

Abstract: This study was conducted to evaluate the efficacy of Effective Microorganisms (EM1 ® ) for inhibiting the growth of some pathogenic bacteria Staphylococcus aureus and E. coli were used in this study and isolated from pathological conditions. These bacteria were diagnosed in laboratory of microbiology, College of Veterinary Medicine, University of Mosul. The colonies that taken from blood agar were 5-7 and cultured in the nutrient broth and incubated at 37 ºC for 24 hours. Bacterial growth was calibrated with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…This might be due to the beneficial effect of the effective microorganisms in the gut of the chickens by suppressing pathogenic bacteria and facilitating digestion and absorption of nutrients. Moreover, others [25] also confirmed that the use of EM at 1% to have the best effect in reducing the growth of pathogenic bacteria. In contrast to the current result, Fathiet al (2018) [26] reported no significant difference in egg production performance among the different dietary treatments.…”
Section: Age At First Egg Laymentioning
confidence: 84%
“…This might be due to the beneficial effect of the effective microorganisms in the gut of the chickens by suppressing pathogenic bacteria and facilitating digestion and absorption of nutrients. Moreover, others [25] also confirmed that the use of EM at 1% to have the best effect in reducing the growth of pathogenic bacteria. In contrast to the current result, Fathiet al (2018) [26] reported no significant difference in egg production performance among the different dietary treatments.…”
Section: Age At First Egg Laymentioning
confidence: 84%
“…Further studies are needed to evaluate EM activity against other pathologic bacteria ( Escherichia coli and Staphylococcus aureus ). Hamad et al [ 36 ] performed microbiological studies with the mentioned bacteria and found an inhibiting role of EM in the growth of pathogenic bacteria. Thus, further studies involving EM in animals are needed, especially in birds, to improve EM as a potential alternative to antibiotics used as growth promoters and to develop future natural production systems.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, milk may have considered to be a serious source of infection by this fungus. Considered the Aspergilli as one of effective fermenting microorganisms which may use for inhibition of pathogenic bacterial growth (23). In addition, (24) mentioned that Aspergillus species was recorded as one cause of urinary system organs, in particular the urinary bladder in calves.…”
Section: Discussionmentioning
confidence: 99%